Information Technologies in Fixing the Evidence in Court - TARASOV, Alexander; YULBERDINA, Lira (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The paper aims to analyze modern combined methods of fixing evidence at the stage of the trial in the criminal process in Russia. For this, the following objectives were defined: to analyze foreign criminal practice, to indicate the shortcomings and prospects for digital technologies implementation in Russian court practice, to compare foreign and Russian legislation relative to the use of information technologies during investigation and proceedings stages, and to develop recommendations. Research methods combine theoretical (comparative and legal) analysis of Russian and foreign legislation were used together with empirical ones (data analysis of the judicial practice cases).Findings: generally accepted forms of conducting criminal proceedings are complicating (online court sessions broadcasting, electronic documents compilation and information storage, combining methods of fixing evidence at various stages of criminal justice). Preserving the written form of keeping the record of a court session, and providing that information and technological means of fixing (video recording and audio protocolling) are necessary. The use of ubiquitous audio or video recording of investigative actions on the one hand will help to avoid numerous procedural mistakes in pre-trial proceedings, providing certain guarantees for the rights of participants in criminal proceedings. The authors propose to supplement Russian criminal procedure legislation and other countries with a number of norms, according to which it is necessary to introduce information fixation means in courts – audio recording or video recording at the trial stage. These means should be used by the court at the request of a defendant and (or) one’s defense counsel.